Trend of Knowledge Transfer Strategy in the Libraries: A Bibliometrics Analysis - Azmir, Aviazka Firdhaussi; Salim, Tamara Adriani (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2024)
This study investigates the significance of knowledge transfer strategies within libraries, encompassing insights and expertise deeply ingrained in organizational strategy. This study aims to explore and evaluate key indicators of scientific behavior in the research domain concerning the intersection of open innovation and concepts of knowledge transfer in libraries. Through bibliometric and network analysis, the study seeks to unravel the joint scientific trajectory of these domains. This research uncovered three primary avenues: knowledge transfer within LIS research and journals, knowledge retention for outgoing employees, and knowledge transfer in information literacy programs. The study reveals publication trends and identifies research gaps, emphasizing opportunities for scholars to contribute to the evolving discourse on knowledge transfer. Practical implications include tailored approaches for organizational learning and innovation. Future research should address identified gaps and explore emerging trends, fostering collaboration between researchers, practitioners, and policymakers to promote organizational resilience and continuous improvement within libraries.